Inching towards Accountability for Quality: Early Days for the Excellent Care for All Act. Issue 2 (July 2014) - Sullivan, Terrence; Brown, Adalsteinn
The Excellent Care for All Act has been in place for 4 years in June 2014. The Act presents a governance imperative to improve quality among health institutions beginning with hospitals and moving forward with organized community, primary, and continuing care sectors. The Act also creates an important new institutional innovation in the form of the provincial agency, Health Quality Ontario, to support the intents of the legislation. This article offers commentary to deepen the effect of the Act through public reporting, broader clinician engagement, and overall evaluation as more organizations are captured in the Excellent Care for All Act's regulatory sweep.